PERBEDAAN GANGGUAN KESEIMBANGAN DITINJAU BERDASARKAN KARAKTERISTIK PASIEN PASCA STROKE DI POLI REHABILITASI MEDIK RSUD ULIN BANJARMASIN - Sandaga, Putri Noor; Siddik, Muhammad; Sanyoto, Didik Dwi; Hayati, Azka; Fakhrurrazy, Fakhrurrazy (Homeostasis, 2024)
Abstract: Stroke causes weakness and results in balance disorders and can affect functional activities. The research aims to determine whether there are differences in balance disorders in post-stroke patients based on patient characteristics. The research was conducted using observational analysis methods and a cross-sectional design. The primary data used is the results of observations of the Berg Balance Scale questionnaire assessment. The research population was post-stroke patients at the Medical Rehabilitation Polytechnic. Number of samples in the period November-December 2023 using purposive sampling technique. The results of the study did not show a relationship between balance disorders in terms of gender, age, stroke onset, lesion location, Brunstrom stage, history of attacks, comorbidities and history of therapy in post-stroke patients. From the results of the study, no relationship was found between mobility impairments based on the characteristics of post-stroke patients at the medical rehabilitation clinic at Ulin District Hospital, Banjarmasin. Keywords: Balance disorders, post-stroke, Berg Balance Scale. Abstrak: Stroke menyebabkan kelemahan dan mengakibatkan gangguan keseimbangan serta dapat mempengaruhi aktivitas fungsional. Penelitian bertujuan mengetahui apakah terdapat perbedaan gangguan keseimbangan pada pasien pasca stroke yang ditinjau berdasarkan karakteristik pasien. Penelitian dilakukan dengan metode analisis observasional dan desain potong lintang. Data primer yang digunakan adalah hasil pengamatan penilaian kuesioner Berg Balance Scale. Populasi penelitian adalah pasien pasca stroke di Poli Rehabilitasi Medik. Jumlah sampel pada periode November-Desember 2023 dengan teknik purposive sampling.  Hasil penelitian tidak di dapatkan hubungan antara gangguan keseimbangan ditinjau dengan jenis kelamin,usia,onset stroke,letak lesi,stadium brunnstrom,riwayat serangan,komorbid dan riwayat terapi pada pasien pasca stroke. Dari hasil penelitian tidak didapatkan hubungan antara gangguan mobilitas ditinjau berdasarkan karakteristik pasien pasca stroke di poli rehabilitasi medik RSUD ulin Banjarmasin. Kata-kata kunci: Gangguan keseimbangan, pasca stroke, Berg Balance Scale.